PRINSIP OTONOMI DALAM PENGELOLAAN KEUANGAN DAERAH PASCA BERLAKUNYA PERATURAN PRESIDEN NOMOR 33 TAHUN 2020 TENTANG STANDAR HARGA SATUAN REGIONAL - Hasyim, Mahrus (Mimbar Keadilan, 2021)
AbstractIndonesia has implemented the principle of regional autonomy as widely as possible, which has been regulated normatively through the formation of applicable laws and regulations, namely Law of the Republic of Indonesia Number 33 of 2004 concerning Regional Autonomy. In more depth, what is meant by autonomy is that in the context of the implementation of regional government in accordance with the mandate of the 1945 Constitution, regional governments regulate and manage government affairs themselves according to the principles of autonomy and co-administration, including in the area of regional financial management. This emerges the latest regulation where there are problems when regional funds and village funds in each region vary greatly in the management of regional financial budgets, as has been issued through Presidential Regulation No. 33/2020 concerning Regional Unit Price Standards. Even so, the regions must make an activity or the effectiveness of regional administration run well in line with regional activities and optimal utilization of regional funds. Of course, this is very interesting when it is assessed that the management of regional finances after the enactment of the Presidential Regulation is a consideration to be able to make the best and most efficient use of regional budget sources. This study uses a normative research approach, because several things are studied in theory, norms, written norms and are a rather conceptual nature of a study. Based on the results of the research, the researcher can find Article 18 paragraph (2) of the 1945 Constitution of the Republic of Indonesia which states that “Provincial, district, and city governments regulate and manage government affairs themselves according to the principles of autonomy and assistance tasks. Each region according to its regional character has different priorities from one region to another in the welfare of the community. The approach taken in the Regional Government Law is an asymmetrical approach, in the sense that the broadest possible autonomy provides different directions from one another according to the needs and characteristics of each region.Keywords: governments; regulated; the principle of regional autonomyAbstrakIndonesia sudah menerapkan prinsip otonomi daerah yang seluas-luasnya, di mana telah diatur secara normatif melalui pembentukan peraturan perundang-undangan yang berlaku, yakni Undang-Undang Republik Indonesia Nomor 33 Tahun 2004 tentang Otonomi Daerah. Secara lebih mendalam otonomi yang dimaksud adalah dalam rangka penyelenggaraan pemerintahan daerah sesuai amanat UUD 1945, pemerintah daerah mengatur dan mengurus sendiri urusan pemerintahan menurut asas otonomi dan tugas pembantuan, termasuk juga dalam hal pengelolaan keuangan daerah. Hal ini muncul peraturan yang terbaru di mana ada problematika ketika dana daerah dan dana desa di masing-masing daerah itu sangatlah berbeda-beda dalam pengelolaan anggaran keuangan daerah, sebagaimana telah dikeluarkan melalui Peraturan Presiden Republik Indonesia Nomor 33 Tahun 2020 tentang Standar Harga Satuan Regional. Meskipun demikian daerah harus membuat suatu kegiatan atau efektifitas penyelenggaraan daerah berjalan dengan baik seiring dengan kegiatan daerah dan pemanfaatan dana daerah yang optimal. Tentunya ini sangat menarik ketika dinilai pengeloaan keuangan daerah pasca berlakunya Peraturan Presiden tersebut menjadi pertimbangan untuk bisa memanfaatkan sumber anggaran daerah dengan sebaik-baiknya dan seefisien mungkin. Penelitian ini menggunakan pendekatan penelitian normatif, dikarenakan beberapa hal dikaji secara teori, kaidah-kaidah, norma-norma yang secara tertulis dan merupakan sifat daripada konseptual dalam suatu penelitian. Berangkat dari hasil penelitian, maka peneliti bisa temukan Pasal 18 ayat (2) Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 disebutkan bahwa “Pemerintahan daerah provinsi, daerah kabupaten, dan kota mengatur dan mengurus sendiri urusan pemerintahan menurut asas otonomi dan tugas pembantuan. Setiap daerah sesuai karakter daerahnya mempunyai prioritas yang berbeda antara daerah satu dan daerah lainnya dalam menyejahterakan masyarakat. Pendekatan yang diambil dalam Undang-Undang Pemerintahan Daerah adalah pendekatan yang bersifat asimetris, dalam artian bahwa otonomi seluas-luasnya memberikan arahan yang berbeda antara satu sama lainnya sesuai dengan kebutuhan dan karakteristik daerah masing-masing.